Isolation and mapping of a mutation in Escherichia coli with altered levels of ribonuclease H. - Carl, P L (1980)
A mutant of Escherichia coli with altered levels of ribonuclease (RNase) H was isolated after mutagenesis with ethyl methane sulfonate. A procedure for assaying RNase H in partially purified extracts was used to screen approximately 1,500 colonies for variations in RNase H activity. Confirmation of a lower level of RNase H in the mutant was accomplished by analysis of RNase H in sodium dodecyl sulfate-polyacrylamide gels. By Hfr, F', and P1 transduction mapping, the genetic locus responsible for the lower levels of RNase H was located at 5.1 min on the E. coli chromosome. This mutation (rnh) represents a new locus on the E. coli chromosome. The only phenotypic characteristic of this mutation which has been observed to date is the lower level of RNase H (30% of parental values).